VARIATIONS IN CLINICAL PRESENTATION, NEUROIMAGING AND EEG PATTERNS OF SUBACUTE SCLEROSING PANENCEPHALITIS: Subacute Sclerosing Panencephalitis Variations - Wasim, Areeba; Alvi, Javeria Raza; Ghani, Natasha; Khalily, Athar; Rehman, Zia Ur; Sultan, Tipu (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the variations in clinical presentation, neuroimaging and electroencephalography patterns of subacute sclerosing panencephalitis. Study Design: Cross-sectional study. Place and Duration of Study: Children’s Hospital & Institute of Child Health, Lahore, Pakistan, from Jul to Dec 2020. Methodology: We recruited children presented with clinical features suggestive of subacute sclerosing panencephalitis, along with positive anti-measles antibodies on cerebrospinal fluid. Association between variables was determined to formulate an early diagnosis of subacute sclerosing panencephalitis. Results: Out of 47 children, 29 were males with a mean age of 6.54 ± 2.9 years. Only 23% were fully immunized against measles, 36.2% were unvaccinated and 40.4% received partial immunization. The mean age of measles infection was 1.49 ± 1.2 years; the mean interval between measles and onset of SSPE was 4.13 ± 3 years. Atypical clinical presentation was seen in 38.3% with intractable epilepsy (8.5%), focal deficit (8.5%) and extrapyramidal symptoms (8.5%) being commonest followed by coma (6.4%), visual loss (4.3%) and psychosis (2.1%). Neuroimaging was suggestive of cortical hyperintensities in 46.8% and was normal in 46.8%. Electroencephalography showed burst suppression in 55.3% and atypical findings in 19.1%. Younger age (1-1.5 years) of measles and unimmunized status were associated with early onset of SSPE with a p-value of 0.001 and 0.05 respectively. Non-immunized status was associated with atypical presentation of SSPE (p-value <0.05). Conclusion: The younger age of measles infection and failure to receive complete immunization led to early onset of Subacute sclerosing panencephalitis with an atypical presentation.